Role of blockages in particle transport through homogeneous granular assemblies. (14th October 2016) - Tejada, I. G.; Sibille, L.; Chareyre, B.
Abstract: This letter deals with the transport of particles through granular assemblies and, specifically, with the intermittent formation of blockages originated from collective and purely mechanical clogging of constrictions. We perform numerical experiments with a micro-hydromechanical model that is able to reproduce the complex interplay between the carrier fluid, the transported particles and the granular assembly. The probability distribution functions (PDFs) of the duration of blockages and displacements give the time scale on which the effect of blockages is erased and the advection-dispersion paradigm is valid. Our experiments show that these PDFs fit exponential laws, reinforcing the idea that the formation and destruction of blockages are homogeneous Poisson processes.